An unsuspected drug target - Murray, Catherine L.; Rice, Charles M. (Nature (London), 2010)
Infection with hepatitis C is one of the main causes of liver disease, yet there are no broadly effective treatments. Discovery of a potent inhibitor of this virus shows that researchers must think outside the box. New drugs for hepatitis C The development of direct-acting antiviral agents to treat chronic hepatitis C virus (HCV) infection, much needed clinically, has focused largely on inhibitors of two viral enzymes, the protease NS3 and NS5B, an RNA-dependent RNA polymerase essential for HCV replication. BMS-790052, identified using chemical genetics as a powerful specific HCV inhibitor, is a small-molecule inhibitor of a third viral molecule that has no known enzyme activity, the non-structural protein 5A (NS5A). A research team from Bristol-Myers Squibb this week reports on the discovery and virological profile of BMS-790052 and discloses clinical trial observations with this compound in normal healthy volunteers and HCV-infected subjects. These results establish proof-of-concept for HCV NS5A inhibition as a clinically relevant mechanism. In vitro data point to synergistic interactions with known HCV inhibitors, suggesting that cocktails of antiviral agents may be a viable therapeutic approach.